African Regional Economic Integration in the Era of Globalisation: Reflecting on the Trials, Tribulations, and Triumphs. Issue 1 (2nd January 2019) - Vhumbunu, Clayton Hazvinei
Abstract: This article examines African regional integration—its birth during the decolonisation phase, its evolution, and the accompanying dynamics—against the background of intensifying globalisation. It critically analyses the complexities associated with African economic integration whilst taking stock of the challenges, successes, and progress made so far. The focus is on analysing how the different—and often-times overlapping—visions, commissions, and omissions of the OAU and AU, political leaders, civil society, and international players have shaped and influenced the nature, form, content, and direction of the continental integration agenda since its inception via-à-vis accelerating globalisation currents. In terms of methodology, secondary data sources are used for analysis. The article argues that, whilst noticeable progress has been made in African regional integration, intensifying globalisation forces are complicating the process. Consequently, economies struggle to cope with increased global competition for trade and investments, the proliferation of multilateral trade agreements, the exposure of vulnerable domestic industries, the weakening capacity of infrastructure, decreasing policy space, and competing interests with regard to decision-making. The findings presented in the article facilitate an understanding of the trials, tribulations, and triumphs of African regional economic integration, which is fundamental in pursuit of the African vision and African dream.